Becoming a Threat: The Burqa and the Contestation Over Public Morality Law in France. Issue 3 (11th December 2014) - Fredette, Jennifer
<x xml:space="preserve">Abstract</x> Through an examination of legislative debate and court opinions, this article illustrates that the French understanding of public order policing as a bulwark of freedom and national sovereignty deeply informed the development of (and contestation surrounding) the 2010 ban on all facial coverings in public. This ban notably includes the burqa or niqab, garments worn by a small minority of Muslim women in France. This article has two aims. The first is to expand on the sociolegal argument about the contested nature of rights protections and constitutional constraints on legislative authority by highlighting how a nation's legal culture can profoundly shape that contestation. The second aim of this article is to show, through a technique called legal archaeology, how longstanding French views on rights confront current European‐inspired alternative views that would give more weight to individualistic protections against state action than has traditionally been the case in France.